COVID-19 vaccine counseling and safety assessment in children and teenagers with underlying medical conditions in China: a single center study. Issue 5 (30th November 2022) - Zeng, Mei; Zhai, Xiaowen; Chang, Hailing; Feng, Tianxing; Zhu, Yanfeng; Ma, Wenjie; Wang, Xiangshi; Ge, Yanling
ABSTRACT: Safety concerns about novel vaccines and necessity of COVID-19 vaccination for children, especially with underlying medical conditions, are the obstacle of COVID-19 vaccination program among pediatric population. The study was conducted to investigate the vaccine hesitancy reasons among the parents, and to monitor the adverse events of inactivated COVID-19 vaccines in children and teenagers with underlying medical conditions in China. Children with underlying medical conditions encountered to the Immunization Advisory Clinic for COVID-19 vaccine counseling were enrolled. They were given immunization recommendation and followed up at 72 h and 28 d after immunization to monitor the immunization compliance after consultation and adverse events. A total of 324 children aged 3–17 y were included. The top three primary medical conditions for counseling were allergy (33.6%), neurological diseases (31.2%) and rheumatic diseases (8.3%). COVID-19 vaccination was promptly recommended for 242 (74.7%) children. Seventy-one (65.7%) children who had allergy issues were recommend to take vaccination, which was significantly lower than that of other medical conditions ( p < .05). The follow-up record showed that 180 children received 340 doses of inactivated COVID-19 vaccine after consultation. Overall, 39 (21.6%) children reported at least one adverse event within 28 d of either vaccination. No serious adverse reactions were observed. No difference of adverse effects between the first dose and the second dose of vaccination except fever. Parents' hesitancy in COVID-19 vaccination for children with underling medical conditions are mainly due to the safety concerns. Specialist consultation is helpful to improve the vaccine uptake.